miR-203 Expression in Exfoliated Cells of Tongue Coating Represents a Sensitive and Specific Biomarker of Gastroesophageal Reflux Disease - Xiuli Yan; Shengliang Zhu; Hui Zhang (Gastroenterology Research and Practice)
Background and Aim. MicroRNAs (miRNAs) have been implicated in the pathophysiology of numerous human diseases including gastroesophageal reflux disease (GERD). The objective of this study was to investigate the miRNA expression of exfoliated cells of the tongue in patients with GERD versus healthy controls (Ctrls). Methods. Using quantitative reverse-transcription PCR (qRT-PCR), expression levels of six candidate miRNAs (miR-143, miR-145, miR-192, miR-194, miR-203, and miR-205) were examined across a discovery cohort of patients with GERD (n=24) versus Ctrls (n=24). These findings were confirmed across a validation cohort (GERD, n=142; Ctrls, n=48). Differences in miRNA expression levels were evaluated using the Mann-Whitney U test while the specificity and sensitivity were obtained using receiver-operator characteristic (ROC) curves. Results. miR-203 was significantly downregulated in GERD patients as compared to Ctrls (P<0.0001) with ROC curve of 0.94 (95% CI: 0.90–0.97). The sensitivity and the specificity of miR-203 were 91.7% and 87.3%, respectively, in the GERD and Ctrls. These results suggest that miR-203 may be a useful diagnostic marker for discriminating GERD from Ctrls. Conclusions. miR-203 testing may assist in the diagnosis of patients with symptoms suggestive of GERD.